Pengaruh Covid-19 Terhadap Kehidupan Masyarakat Indonesia: Sektor Pendidikan, Ekonomi Dan Spiritual Keagamaan - Putra, M. Wahyu Pratama; Kasmiarno, Kurnia Sari (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
The Covid-19 has been able to affect the joints life in the wider community, especially in Indonesia. Starting from the education sector, the economy, to the spiritual sector of religious communities in carrying out worship. The research was conducted qualitatively with sources from literature and strengthened by structured interviews with several people who works in the sectors raised. This study describes people’s live related to the changes they fell, the impacts and traumas they face, how they survive and the lessons learned in all the limitations caused by the pandemic. The results obtained in this study was that in the education sector there is an online system, with a less effect impact. Meanwhile, the economic sector changes society to be more creative, but it still has an impact on decreasing income. On the spiritual side, religion forms religious activities to adapt to circumstances, which have an impact on religious activities at home, live streaming, etc. In addition, the trauma experienced is in the form of fear of contracting the Covid virus. However, they still survive by studying independently, reducing costs and increasing worship. The wisdom gained from this pandemic is to gather more often with family, be more creative, be more devoted in worship and cultivate a spirit of mutual help.